Cognitive impairments associated with medial temporal atrophy and white matter hyperintensities: an MRI study in memory clinic patients - Overdorp, Eduard J.; Kessels, Roy P. C.; Claassen, Jurgen A.; Oosterman, Joukje M. (Frontiers in Aging Neuroscience, 2014)
In this retrospective study, we investigated the independent effects of white matter hyperintensities and hippocampal atrophy on cognitive functions in a broad sample of patients seen in a memory clinic. To ensure generalizability, these associations were examined irrespective of diagnosis and with minimal exclusion criteria. Next to these independent effects, interactions between white matter hyperintensities and hippocampal atrophy were examined. Between January 2006 and September 2011 a total of 500 patients visited the memory clinic, 397 of whom were included. Magnetic resonance images of 397 patients were visually analyzed for white matter hyperintensities (WMH), medial temporal atrophy (MTA) and global atrophy. We evaluated the association of WMH and MTA with the following cognitive domains: global cognition, episodic memory, working memory, executive function and psychomotor speed. Main effects and interaction effects were examined by means of correlation and regression analyses. In the regression analyses, we controlled for potential confounding effects of global atrophy. The correlational results revealed that WMH were associated with global cognition, executive function and psychomotor speed, whereas a trend was found for episodic memory. MTA was associated with all these four cognitive domains; an additional trend was observed for working memory. Hierarchical regression analyses revealed main independent effects of MTA for episodic memory, executive function, psychomotor speed and global cognition; WMH were only associated with global cognition. The interaction between MTA and WMH was significant for episodic memory only. This study demonstrates that predominantly MTA is an independent predictor not only for memory function, with which is it classically associated, but also for global cognition and executive function. Taken together, MTA may be an important correlate of cognitive deficits found in people attending the memory clinic.